Antibodies as an unlimited source of anti-infective, anti-tumour and immunomodulatory peptides. (1st September 2014) - Ciociola, Tecla; Magliani, Walter; Giovati, Laura; Sperindè, Martina; Santinoli, Claudia; Conti, Giorgio; Conti, Stefania; Polonelli, Luciano
Antibodies (Abs) are emerging as an important class of therapeutic agents for the treatment of various human diseases, often conjugated to drugs or toxic substances. In recent years, the incidence of cancer and infectious diseases has increased dramatically, making it imperative to discover new effective therapeutic molecules. Among these, small peptides are arousing great interest. Synthetic peptides, representative of variable and constant region fragments of Abs, were proved to exert in vitro, ex vivo and/or in vivo anti-microbial, anti-viral, anti-tumour and/or immunomodulatory activities, mediated by different mechanisms of action and regardless of the specificity and isotype of the Ab. Some of these synthetic peptides possess the ability to spontaneously and reversibly self-assemble in an organised network of fibril-like structure. Ab fragments may represent a novel model of targeted anti-infective and anti-tumour auto-delivering drugs.